(untitled) (Research, Society and Development, 2022)
Periodontal Disease (PD) is an infectious and inflammatory condition that affects the oral cavity and is considered a risk factor for other systemic diseases, such as Bacterial Endocarditis (EB), due to the variety of pathogens that can cause bacteremia and colonize cardiac sites. Objective: To report a case about the relationship between PD and EB. Methodology: We report the case of a 53 year old patient, R.N.S., who sought medical attention after an afternoon fever and weight loss, and was diagnosed with pulmonary and urinary tract infection. After nine days, he was transferred to a High Complexity Hospital, and diagnosed with infective endocarditis with vegetation in the mitral valve, caloric malnutrition, and Acute Respiratory Syndrome. After 24 hours, he was referred to the Intensive Care Unit with tachypnea, drop in saturation, and mental confusion. After blood culture, the diagnosis was fungal infectious endocarditis by Candida tropicalis, with ventricular dysfunction. The dental evaluation showed a partial edentulous patient, calculus and dental biofilm, gingival recession on tooth 13, mobility on 31 and 32. Subgingival root scraping/straightening and exodontia of the 31 and 32 were performed in the operating room prior to cardiac surgery. Serratia marcescens was isolated from the culture of the periodontal abscess of tooth 13. The patient evolved without positive results for fungi in blood, tracheal secretion or urine culture. However, the same bacteria (S. marcescens) was present in blood and mitral valve samples. Conclusion: Dental evaluation should precede cardiac surgeries to avoid that oral infectious foci serve as a reservoir for opportunistic bacteria that may contribute to unfavorable outcomes such as EB by systemic dissemination of these pathogens.